2019
DOI: 10.1016/j.jretconser.2019.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Consumption dynamics during recession and recovery: A learning journey

Abstract: This paper original contribution builds on examining consumer attitudes in periods of recession and post-recession, providing new insights concerning consumer decision-making, the new logic of spending and saving behavior and also opening new paths for research on the psychology of choice in contexts of recession and the immediate stage of recovery. The study used a longitudinal qualitative approach comprising twenty-two semi-structured interviews with eleven Portuguese consumers. The research was conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 42 publications
2
43
1
Order By: Relevance
“…In Greece, during the 2007–2017 economic crisis, the quantities of food consumed fell significantly, with consumers opting increasingly for less expensive brands [ 36 ]. The same trend towards a preference for generic products and cheaper brands was also reported during the Asian crisis [ 29 ] and the recession in Portugal resulting from the 2007–2017 crisis [ 37 ]. Specifically, during the economic crisis in Spain, it was found that consumers noticeably moved towards lower-priced retail outlets [ 38 ].…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…In Greece, during the 2007–2017 economic crisis, the quantities of food consumed fell significantly, with consumers opting increasingly for less expensive brands [ 36 ]. The same trend towards a preference for generic products and cheaper brands was also reported during the Asian crisis [ 29 ] and the recession in Portugal resulting from the 2007–2017 crisis [ 37 ]. Specifically, during the economic crisis in Spain, it was found that consumers noticeably moved towards lower-priced retail outlets [ 38 ].…”
Section: Introductionsupporting
confidence: 57%
“…The difference in lamb meat consumers’ preferences between 2004 and 2014 lies in the significance attached to price, with this being the fourth most important in 2004 but the second in importance in 2014. This change in the level of importance is probably due to the financial crisis affecting Spain between 2007 and 2017, given that, as reported in previous studies on periods of economic crisis, consumers are more sensitive to price [ 29 , 36 , 37 ]. A decrease in the quantities of food consumed and in the food spending because of the crisis were reported in Spain [ 43 ] with similar results in Greece [ 36 ].…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…This study contributes further empirical evidence that marketing environment shifts can substantially alter consumer search and decisions processes on a permanent basis. Sarmento et al (2019) recently showed that economic recessions serve to reshape consumer preferences over the long-term. Evolution in consumer capabilities and tendencies to engage in information search with mobile technologies during brick-and-mortar shopping trips further indicate that fundamental shifts are on the horizon for retailers.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we assume that a lower level of electricity demand will remain persistent over the course of the five years after the start of COVID-19 driven crisis. These dynamics could also trigger more efficient energy demand and electricity consumption in postpandemic times [33]. We thus assume that the drop in electricity demand by 5% at the beginning of 2021 remains persistent until 2050.…”
Section: "Gradual Recovery " Scenariomentioning
confidence: 99%